2004
DOI: 10.1161/01.cir.0000147612.59751.4c
|View full text |Cite
|
Sign up to set email alerts
|

Right Ventricular Enlargement on Chest Computed Tomography

Abstract: Background-In patients with acute pulmonary embolism (PE), rapid and accurate risk assessment is paramount in selecting the appropriate treatment strategy. Right ventricular (RV) enlargement on chest CT has previously been shown to correlate with an unstable hospital course, but its role as a predictor of death is unknown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
115
1
13

Year Published

2005
2005
2013
2013

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 448 publications
(133 citation statements)
references
References 25 publications
4
115
1
13
Order By: Relevance
“…Several previous studies have suggested that pulmonary arterial embolic burden assessed by CT as well as by RV/LV ratio is also a predictor for APTE patients (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). On the other hand, Ghaye et al (19) suggested that RV/LV diameter ratio and azygos vein diameter were significant predictors, and that pulmonary arterial embolic burden was not.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…Several previous studies have suggested that pulmonary arterial embolic burden assessed by CT as well as by RV/LV ratio is also a predictor for APTE patients (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). On the other hand, Ghaye et al (19) suggested that RV/LV diameter ratio and azygos vein diameter were significant predictors, and that pulmonary arterial embolic burden was not.…”
Section: Discussionmentioning
confidence: 98%
“…According to the past literatures (14)(15)(16)(17)(18)(19)(20), the scans were evaluated by measuring the minor axes of the right and left ventricles of the heart in the transverse plane at their widest points between the inner surface of the free wall and the surface of the interventricular septum. These maximum dimensions may be found at different levels.…”
Section: Contrast-enhanced Ctmentioning
confidence: 99%
See 3 more Smart Citations